Dewetting of Co Thin Films Obtained by Atomic Layer Deposition Due to the Thermal Reduction Process - Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D (Cambridge University Press, 2017)
Cobalt oxide thin films with different thicknesses were synthesized by atomic layer deposition. After a thermal reduction process, under a controlled atmosphere of hydrogen, it was possible to convert cobalt oxide to metallic cobalt. The different thicknesses were obtained considering from 500 to 2000 cycles of CoCp2/O3. The thin films were characterized by x-ray diffraction, scanning electron microscopy, energy-dispersive x-ray microanalysis, and by magneto-optical Kerr effect measurements. The indirect synthesis process allows us to obtain cobalt oxide and cobalt thin films with controlled thicknesses and extraordinary magnetic properties, with coercivities above 500 Oe. Copyright © Materials Research Society 2017.